2017
DOI: 10.1098/rsif.2016.0657
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide coatings for hydroxyapatite: electrostatic and covalent attachment of antimicrobial peptides to surfaces

Abstract: The interface between implanted devices and their host tissue is complex and is often optimized for maximal integration and cell adhesion. However, this also gives a surface suitable for bacterial colonization. We have developed a novel method of modifying the surface at the material-tissue interface with an antimicrobial peptide (AMP) coating to allow cell attachment while inhibiting bacterial colonization. The technology reported here is a dual AMP coating. The dual coating consists of AMPs covalently bonded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 54 publications
0
39
0
2
Order By: Relevance
“…The authors demonstrated that after 3 weeks, since the infection initiation and 12 weeks of treatment with vancomycin loaded nanoHAp/collagen/calcium sulfate composite, no evidence of infection was observed, while the formation of new trabecular bone was noticed at the implantation site. Furthermore, Townsend et al [72] accomplished by a dual approach-covalently bonding of antimicrobial peptide (AMP) to HAp, followed by deposition of electrostatically bound AMPs-an effective coating design, which was proven to be stable for a period of over 12 months and had the potential to prevent implant colonization by both Gram-positive (S. aureus and Staphylococcus epidermidis) and Gram-negative (P. aeruginosa) bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated that after 3 weeks, since the infection initiation and 12 weeks of treatment with vancomycin loaded nanoHAp/collagen/calcium sulfate composite, no evidence of infection was observed, while the formation of new trabecular bone was noticed at the implantation site. Furthermore, Townsend et al [72] accomplished by a dual approach-covalently bonding of antimicrobial peptide (AMP) to HAp, followed by deposition of electrostatically bound AMPs-an effective coating design, which was proven to be stable for a period of over 12 months and had the potential to prevent implant colonization by both Gram-positive (S. aureus and Staphylococcus epidermidis) and Gram-negative (P. aeruginosa) bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Silver (Jones et al, 2006) quaternary ammonium compounds (Ravikumar et al, 2006), salicylic acid (Bryers et al, 2006) or polymeric substances (Siedenbiedel and Tiller, 2012) are highly effective in vitro, but use of these chemicals can induce toxicity in vivo (Ramstedt et al, 2009). Loss of activity and the inability to sterilize surfaces once antimicrobials are covalently bound to devices are also problems associated with antimicrobial coatings (Vasilev et al, 2009;Townsend et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to many years of research, protease inhibitors have gained the status of registered drugs and have been successfully used in the treatment of diseases caused by HIV, influenza, or HCV virus [30][31][32]. Currently, many biologically active substances covalently immobilized on the surface of biomaterials are known [9,[12][13][14][15][16][17][33][34][35]. Therefore, we decided to perform covalent immobilization of three serine protease inhibitors, one synthetic (AEBSF) and two natural (soy inhibitor and α 1 -antitrypsin), on the surface of biomaterials that are commonly used in regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%